Dharmavidya’s Engagement with Honen: How a Contemporary British Pureland Buddhist Teacher retrieves his Japanese Spiritual Heritage - Ollier, Richard (Journal of global buddhism, 2018)
The Pureland Buddhism of the contemporary British teacher and writer Dharmavidya David Brazier has been directly influenced by that of the medieval Japanese thinker, Hōnen. This article investigates the nature of this influence through an examination of two short texts, Dharmavidya’s Summary of Faith and Practice and Hōnen’s Ichimai Kishōmon. It suggests that the relationship between the two pieces of writing can be clarified by applying to them not only the traditional Buddhist concepts of upāya and senju , but also theoretical perspectives drawn from the work of the post-modernist philosopher and religious commentator, John D. Caputo. This approach shows that Dharmavidya leaves ‘open’ what the Pureland ritual of nembutsu chanting might mean for the devotees who practice it. The article also contends that, under Hōnen’s influence, Dharmavidya has produced a text that is radical and ‘post-secular’ in commending devotion rather than meditation as the primary practice of his Order of predominantly ‘Convert’ Buddhists.